Ambivalência e relativismo nos Dissoi logoi - Giovanio Aguiar (2006)
This thesis reconstructs the argument of the Dissoi Logoi, investigating in them the scope of their ethical and political ambivalence and relativism. We propose a critical presentation of the text, by articulating a historical approach to a conceptual one. We refer to other ancient texts, such as Górgias´, Plato´s and Aristotle´s, as well as to contemporary interpreters to discuss concepts such as logos, nomos, antilogía, arete, Mnemosune and kairos. We come to the conclusion that the Dissoi Logoi are a manual of argumentation which aims at potentializing ethical and political action.